Glucose deposited during goose fatty liver formation inhibits inflammation in goose fatty liver by reducing the interaction between PKA and IκB - Mengqing Lv; Jiahui Li; Ya Xing; Xiaoyi Zhou; Jing Ge; Tuoyu Geng; Daoqing Gong; Minmeng Zhao (Poultry Science)
Protein Kinase A (PKA) is found in a wide range of body tissues and is involved in various cellular activities. PKA has been observed to interact with key proteins in the nuclear factor kappa-B (NF-κB) pathway to activate the pathway, thereby triggering an inflammatory response. However, the role of PKA in the anti-inflammatory mechanism of goose fatty liver remains to be elucidated. A total of 16 healthy 70-day-old male Lander geese were randomly divided into the control and overfeeding groups. Next, goose primary hepatocytes were treated with 200 mmol/L glucose. The protein levels of p-IκB, PKA and tumor necrosis factor alpha (TNFα) in the liver and hepatocytes, as well as the interaction of p-IκB and PKA were detected. Finally, the hepatocytes were treated with a combination of 200 mmol/L glucose and overexpressed or knocked-down PKA. The protein levels of p-IκB, PKA and TNFα were measured. The results showed that the levels of p-IκB, PKA and TNFα were significantly reduced (P < 0.05) in goose fatty liver compared to normal liver, and the interaction of p-IκB and PKA was inhibited in overfeeding group. The levels of p-IκB and PKA in 200 mmol/L glucose-treated hepatocytes were significantly reduced compared with control group (P < 0.05). Furthermore, the level of TNFα was unchanged (P > 0.05), and the interaction of p-IκB and PKA was inhibited in 200 mmol/L glucose-treated hepatocytes. The levels of p-IκB, PKA, and TNFα were significantly increased in the hepatocytes overexpressing PKA and treated with 200 mmol/L glucose compared to control group (P < 0.05). In contrast, the levels of p-IκB, PKA, and TNFα were significantly suppressed in the knockdown of PKA and treated with 200 mmol/L glucose compared with control group (P < 0.05). In conclusion, inflammation was suppressed in both the goose fatty liver and the hepatocytes treated with 200 mmol/L glucose. In addition, glucose inhibits inflammation in goose fatty liver by reducing the interaction between PKA and IκB.